2013
DOI: 10.1155/2013/370715
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Pathophysiological Activities of the Cardiac Molecule Cardiotrophin-1 in Obesity

Abstract: Cardiotrophin-1 (CT-1) is a heart-targeting cytokine that has been reported to exert a variety of activities also in other organs such as the liver, adipose tissue, and atherosclerotic arteries. CT-1 has been shown to induce these effects via binding to a transmembrane receptor, comprising the leukaemia inhibitory factor receptor (LIFRβ) subunit and the glycoprotein 130 (gp130, a common signal transducer). Both local and systemic concentrations of CT-1 have been shown to potentially play a critical role in obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“… 21 In addition, accordingly with the role of CT-1 as multifunctional cytokine, several authors reported its participation in the regulation of glucose and lipid metabolism. 22 25 …”
Section: Introductionmentioning
confidence: 99%
“… 21 In addition, accordingly with the role of CT-1 as multifunctional cytokine, several authors reported its participation in the regulation of glucose and lipid metabolism. 22 25 …”
Section: Introductionmentioning
confidence: 99%
“…CT-1 reduces fatty acid synthesis and insulin receptor substrate-1 expression, and induces insulin resistance in adipocytes in vitro [55]. Exogenous CT-1 administration into mice increases energy expenditure, fatty acid oxidation, and glucose cellular uptake [56]. Chronic administration of CT-1 increases lipolysis, fatty acid oxidation, mitochondrial biogenesis, and adipocyte shrinkage [56].…”
Section: Roles Of Ct-1 In Metabolic Syndromementioning
confidence: 99%
“…Exogenous CT-1 administration into mice increases energy expenditure, fatty acid oxidation, and glucose cellular uptake [56]. Chronic administration of CT-1 increases lipolysis, fatty acid oxidation, mitochondrial biogenesis, and adipocyte shrinkage [56]. However, the relationship between the in vitro and in vivo effects of CT-1 and its plasma concentrations in human metabolic diseases remains unknown so far.…”
Section: Roles Of Ct-1 In Metabolic Syndromementioning
confidence: 99%
“…It acquired its name from the capability to induce a hypertrophic response in neonatal cardiac myocytes [7]. It is one of the pro-in ammatory cytokines belonging to the IL-6 cytokine superfamily that has been showed to do a diversity of actions in many organs such as the heart, liver, adipose tissue, and atherosclerotic arteries [8]. Growing evidence showed increased circulating CT-1 levels in humans with obesity [9] and type 2 diabetes [10], advocating that CT-1 may play a pathophysiological role in obesityrelated complications.…”
Section: Introductionmentioning
confidence: 99%